2019
DOI: 10.1002/anie.201812894
|View full text |Cite
|
Sign up to set email alerts
|

Stereoinversion of Unactivated Alcohols by Tethered Sulfonamides

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Despite these recent advances emphasized above, there are no reported methods on either the synthesis of non-allylic six-membered heterocyclic compounds through intramolecular substitution of the OH group or the direct intramolecular substitution of tertiary alcohols with chirality transfers, or the use of substrates containing weak nucleophiles (such as phenolic OH) 28 . In order to offer a synthetic route to overcome these limitations, we continued our efforts on acid-catalyzed transformations and report herein a Fe(OTf) 3 -catalyzed intramolecular substitution of enantioenriched secondary and tertiary alcohols by N- , O- and S- centered nucleophiles with high degree of chirality transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recent advances emphasized above, there are no reported methods on either the synthesis of non-allylic six-membered heterocyclic compounds through intramolecular substitution of the OH group or the direct intramolecular substitution of tertiary alcohols with chirality transfers, or the use of substrates containing weak nucleophiles (such as phenolic OH) 28 . In order to offer a synthetic route to overcome these limitations, we continued our efforts on acid-catalyzed transformations and report herein a Fe(OTf) 3 -catalyzed intramolecular substitution of enantioenriched secondary and tertiary alcohols by N- , O- and S- centered nucleophiles with high degree of chirality transfer.…”
Section: Introductionmentioning
confidence: 99%
“…A conceptually different approach to catalytic nucleophilic substitution termed "borrowing hydrogen" (16)(17)(18) involves oxidation of the alcohol, condensation with a nucleophile, and then reduction to achieve the product of a direct substitution reaction. Despite these advances, the development of catalytic methods that enable stereospecific bimolecular substitution of nonactivated chiral alcohols remains a major challenge (19,20). Although some progress has been made by using cyclopropenone catalysis (21), most effort to date has been focused on modifying the original Mitsunobu protocol by redox recycling of the stoichiometric reagents.…”
mentioning
confidence: 99%
“…Enantiopure chiral substrates were also used by Baik, Cook and co-workers to develop iron(III)-catalyzed stereospecific nucleophilic substitutions [ 77 ]. Preliminary studies on intermolecular amination reactions of secondary and tertiary alcohols demonstrated the efficiency of iron catalysts, which afforded the corresponding desired products in high yields.…”
Section: Othersmentioning
confidence: 99%